Remission of Thyrotoxicosis during Treatment with Propranolol - McLarty, D. G. (1973)
Twenty-eight thyrotoxic patients were treated with propranolol. In seven patients the drug had to be discontinued after one or two months, but in the remaining 21 clinical improvement was observed. Serial clinical studies and tests of thyroid function performed at monthly intervals showed that in four patients thyrotoxicosis remitted and all indices of thyroid function returned to normal. A fifth patient shows distinct evidence of remission with the 20-minute (132)I uptake falling to normal, although the free-thyroxine index remains slightly raised. It is likely that these remissions reflect the natural tendency of the disease to remit since propranolol is not considered to have any direct in-vivo effect on thyroid function. However, because of failure to gain adequate control of symptoms in all patients treated, and the fact that circulating thyroid hormone levels were often not restored to normal, propranolol is considered an unsatisfactory alternative to conventional antithyroid drugs for routine treatment.